Genetic anchoring of whole-genome shotgun assemblies - Mascher, Martin; Stein, Nils (Frontiers in Genetics, 2014)
The recent advances in sequencing throughput and genome assembly algorithms have established whole-genome shotgun (WGS) assemblies as the cornerstone of the genomic infrastructure for many species. WGS assemblies can be constructed with comparative ease and give a comprehensive representation of the gene space even of large and complex genomes. One major obstacle in utilizing WGS assemblies for important research applications such as gene isolation or comparative genomics has been the lack of chromosomal positioning and contextualization of short sequence contigs. Assigning chromosomal locations to sequence contigs required the construction and integration of genome-wide physical maps and dense genetic linkage maps as well as synteny to model species. Recently, methods to rapidly construct ultra-dense linkage maps encompassing millions of genetic markers from WGS sequencing data of segregating populations have made possible the direct assignment of genetic positions to short sequence contigs. Here, we review recent developments in the integration of WGS assemblies and sequence-based linkage maps, discuss challenges for further improvement of the methodology and outline possible applications building on genetically anchored WGS assemblies.